(untitled) (Scientific electronic journal "Labor Economics and Human Capital", 2024)
This article highlights the socio-economic significance and specific features of the development of women’s leadership skills in higher education institutions, the experiences of women’s leadership development in foreign countries, and the possibilities of their application in our republic. Also, on the basis of the questionnaire, the factors hindering the leadership of women studying in higher education institutions and working in high management positions were studied, they were analyzed in the regions of the republic and conclusions were given.